Health Patterns Reveal Interdependent Needs of Dutch Homeless Service Users - Everdingen, Coline van; Peerenboom, Peter Bob; Velden, Koos van der; Delespaul, Philippe (Frontiers in Psychiatry, 2021)
Background: Homelessness is an increasing problem in Western European countries. Dutch local authorities initiated cross-sectional research to obtain accurate health and needs information on Homeless Service (HS) users. Methods: The Homeless People Treatment and Recovery (HOP-TR) study uses a comprehensive assessment strategy to obtain health data. Using a meta-snowball sampling in 2015-2017, 436 Dutch HS users were assessed. Relevant information in all areas of life was collected in semi-structured interviews and standard questionnaires. The lived experience of HS users was the primary source and enriched with professional assessments. The strategy for mental health was transdiagnostic. The positive health framework was used to structure the domains of symptomatic, functional, social, and existential health data to assess recovery aspects. Results: Most subjects were males, low educated, with a migration background. The majority were chronically or intermittently homeless. Concurrent health problems touched at least two domains in nearly all subjects (94.7%). Almost all participants showed mental health problems (98.6%). Frequent comorbid conditions were addiction (78%), chronic physical conditions (59.2%), and intellectual impairments (39.9%). A significant share had a severe mental disease (72.5%). Conclusion: The HOP-TR study reveals significant rates of concurrent health problems among Dutch HS users. The problems’ interdependent character underlines the need for an integrated 3-D recovery-oriented public health approach.